(untitled) (Scientific journal of the Fergana State University, 2025)
The formation of membrane transition channels is associated with various external conditions, mechanical forces, and changes in membrane structure. This article analyzes the formation of channels in membranes under the influence of electric fields, the significance of channel size, and other factors. A deeper understanding of these processes may lead to new approaches in cell biology and medicine.